2001
DOI: 10.1007/s007870170049
|View full text |Cite
|
Sign up to set email alerts
|

Autistic disorder versus other pervasive developmental disorders in young children: same or different?

Abstract: Eighteen preschool children diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders Third Edition Revised (DSM III-R) as having Pervasive Developmental Disorder-Not Otherwise Specified (PDD-NOS) were compared to 176 children with DSM III-R Autistic Disorder (AD), and to 311 non-autistic children with developmental language disorders (DLD) (N = 201) or low IQ (N = 110). All children were partitioned into "high" and "low" cognitive subgroups at a nonverbal IQ of 80. Within cognitive subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…Thus, from a clinical standpoint, children whose PDD-NOS diagnosis was established before 36 months should be re-assessed at a later age (Rondeau et al, 2010). Similar to previous reports (Allen et al, 2001, deBruin et al, 2006, Matson, et al, 2007, Szatmari et al 2002, in our study (Karabekiroglu & Akbas, in press) mental retardation was significantly more prevalent in the autism than in the PDD-NOS or ADHD groups. Several investigators suggested that exploring the presence of mental retardation may be more useful in terms of planning treatment and predicting outcome than a classification based on symptom number alone (Szatmari et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, from a clinical standpoint, children whose PDD-NOS diagnosis was established before 36 months should be re-assessed at a later age (Rondeau et al, 2010). Similar to previous reports (Allen et al, 2001, deBruin et al, 2006, Matson, et al, 2007, Szatmari et al 2002, in our study (Karabekiroglu & Akbas, in press) mental retardation was significantly more prevalent in the autism than in the PDD-NOS or ADHD groups. Several investigators suggested that exploring the presence of mental retardation may be more useful in terms of planning treatment and predicting outcome than a classification based on symptom number alone (Szatmari et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…It was concluded that based on intelligence scores, only PDD-NOS and ADHD emerged as distinct categories, whereas the combined diagnosis did not. Allen et al (2001) compared 18 preschool children with PDD-NOS to 176 children with autistic disorder and 311 non-autistic children with developmental language disorders (DLD) (N = 201) or low IQ (N = 110). The children with PDD-NOS did not differ significantly from either the children with autism or the children with DLD in verbal and adaptive skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes in clinical observations have led to the classification of autism as a spectrum disorder, autism spectrum disorder (ASD), which describes a group of developmental disorders characterized by impairments in reciprocal social interaction and verbal and nonverbal communication skills compounded by symptoms of restrictive and repetitive behaviors and/or stereotyped patterns of interest that are abnormal in their intensity or focus [4][5][6][7] . Included in this spectrum is 'classical' autism, which usually involves the stereotypical social isolation, impaired verbal communication and repetitive behaviors; Asperger syndrome, often described as a milder form of autism, lacking the components of intense repetitive behaviors and social withdrawal; and pervasive developmental disorder, which usually encompasses disorders that cannot otherwise be classified [2,[7][8][9] .…”
mentioning
confidence: 99%